Pengaruh Penambahan Vitamin C Dosis Berbeda Terhadap Pertumbuhan Dan Kelangsungan Hidup Ikan Nila (Oreochromis niloticus) Betina - Sumaraw, Audi Yoel; Mulis; Ahmad, Indra G (ACROPORA: Jurnal Ilmu Kelautan dan Perikanan Papua, 2024)
Artifficial fee nutrition can be enhanched by adding vitamin C, aiming to suport the growth and survival of female Nile tilapia (Oreochromos niloticus). The addition of vitamin C to feed for the growht an d survival of fish has been extensively studied. However, there is still limited research specifically focusing on female Nile tilapia. The study aims to investigate the effect of vitamin C supplementation in feedd and to determine the optimal dosage for the growth and survival of fimale Nile tilapia juveniles. The research adopts an experimental approach using a Completely Randomized Design (CRD), consisting of 4 treatments and 3 replications. The treatments include A (Vitamin C 200 mg/kg feed), B (Vitamin C 300 mg/kg feed), C (Vitamin C 400 mg/kg feed) and D (Without vitamin C supplementation). Based on the results, the treatment with 300 mg/kg feed provide the best outcome, followed by treatment A and treatment C. The ANOVA analysis results indicate that there is no significant effect on growth (Fcount < Ftable) with a significance value >0.05, while there is a significant effect on survival (Fcount > Ftable) with a significance value < 0.05. Therefore, it is concluded that adding vitamin C to feed does not significantly affect the growth of female Nile tilapia juveniles but results in better growth compared to not providing vitamin C. In addition, of vitamin C significantly affects survival. Keywords: Female Nile Tilapia, Growth and Survival, Vitamin C